1987
DOI: 10.1007/bf00635370
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal capacity of employees aged 44 to 58 years in physical, mental and mixed types of work

Abstract: The musculoskeletal capacity of 60 women and 69 men, average age 52.3 +/- 3.7 years was determined, including measurements of anthropometry, maximal isometric trunk flexion and extension, sit-ups, isometric hand grip strength and back mobility. According to the job and to cluster analysis, the subjects were divided into three dominating work groups; physical, mental, and mixed groups. The results showed significant differences in right hand grip strength of the women and in the number of sit-ups by men among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
2
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 13 publications
2
19
2
1
Order By: Relevance
“…Furthermore, most of the ''cases'' were also found to have low muscle endurance (which correlates to aerobic capacity), as well as poor balance and coordination. Earlier studies have shown a negative relationship between capacity (both aerobic and muscular strength) and long-lasting physical activity at work (Nyga˚rd et al 1987(Nyga˚rd et al , 1988Era 1992;Torge´n et al 1999). Females in the highest quartile of TWA-MET work had, however, lower muscle endurance in their abdomen and legs and worse coordination than subjects in the lowest quartile of TWA-MET work .…”
Section: Physical Demands and Physical Capacitymentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, most of the ''cases'' were also found to have low muscle endurance (which correlates to aerobic capacity), as well as poor balance and coordination. Earlier studies have shown a negative relationship between capacity (both aerobic and muscular strength) and long-lasting physical activity at work (Nyga˚rd et al 1987(Nyga˚rd et al , 1988Era 1992;Torge´n et al 1999). Females in the highest quartile of TWA-MET work had, however, lower muscle endurance in their abdomen and legs and worse coordination than subjects in the lowest quartile of TWA-MET work .…”
Section: Physical Demands and Physical Capacitymentioning
confidence: 86%
“…A positive relationship between physical capacity and physical workload among young workers has been documented (Schibye et al 2001). In studies among middle-aged and elderly workers who have had physically strenuous jobs during their careers, a negative relationship between capacity and physical activities at work has been observed (Nyga˚rd et al 1987(Nyga˚rd et al , 1988Era 1992;Miettinen and Louhevaara 1994). In contrast to these findings, other studies find a positive relationship between muscle strength and workload among elderly workers (e.g.…”
Section: Introductionmentioning
confidence: 89%
“…Some studies found a tendency to lower maximal muscle strength in the hand, back and abdomen among workers having physically heavy work (Era et al 1992;Karlqvist et al 2003;Ruzic et al 2003;Nyga˚rd et al 1987Nyga˚rd et al , 1998aNyga˚rd et al , 1998bSøgaard et al 1996). These studies indicated that physically heavy work is no guarantee for high physical capacities.…”
Section: Introductionmentioning
confidence: 85%
“…A positive relationship between physical aerobic capacity and physical workload has been documented for young workers (20). In studies among middle-aged and elderly workers who have had physically strenuous jobs during their careers, a negative relationship has been observed between aerobic capacity and physical activities at work (21)(22)(23)(24). In contrast to these findings, other studies have found a positive relationship between muscle strength and workload among elderly workers (20).…”
mentioning
confidence: 97%